Review on natural plant fibres and their hybrid composites for structural applications: Recent trends and future perspectives - Ismail, Sikiru Oluwarotimi; Akpan, Emmanuel; Dhakal, Hom N. (Composites. Part C, Open access, 2022)
•Conceptual design strategies are needed to balance cost, sustainability and performance of natural FRP hybrid composites.•Better scientific understanding of failure modes and damage mechanisms is a major requirement for further developement of natural FRP hybrid composites.•Property prediction in natural FRP hybrid composites is of high importance.•Understanding the concept behind synergistic effect is important for further development of natural FRP composites for advanced applications. Sustainability and environmental protection have given rise to the use of renewable and biobased materials in several application areas. Fibre reinforced composites are currently gaining a high market value in both structural and semi-structural applications. Making these materials environmentally friendly, renewable and lighter will protect the environment and increase resource use efficiency. Opposed to synthetic fibres such as carbon and glass, natural plant fibres are less expensive, lighter, degradable, easy to produce, non-toxic and environmentally friendly. However, natural plant fibres are inferior to their synthetic counterparts in both mechanical performance and tolerance to harsh environmental conditions. One method of compensating for these disadvantages is to combine natural and synthetic fibres in a single matrix forming a hybrid composite where the disadvantages of one are compensated by the other. In this way, sustainability and cost minimisation are achieved with acceptable mechanical and physical responses. However, successful implementation and advancement in the development of natural plant fibre reinforced polymer (FRP) hybrid composites require the development of workable conceptual design, suitable manufacturing techniques and understanding of the strengthening mechanisms. The main objectives of this review are to critically review the current state of knowledge in the development of natural FRP hybrid composites, outlining their properties and enhancing them while reducing environmental impact of the product through the hybridisation approach.